STUDI ALTERNATIF PENGENDALIAN BANJIR SUNGAI TONDANO DI KOTA MANADO - J.B. Nanlohy, Benjamin; Jayadi, Rachmad; Istiarto, Istiarto (Civil Engineering Forum Teknik Sipil, 2008)
Tondano River, along with its tributary Tikala River, is very potential to cause flood in Manado City. There were three big floods occurred in 1996, 2000 and 2005. In order to mitigate the damage risk due to flood, the controlling effort that can be applied soon in the field is required through short term flood control plan using structural measures. The feasible alternative plans should be evaluated to define the best plan based both on the hydraulics point of view and their effects on the river uses. The study is carried out through the 5 year return period flood routing using the version 3.1 HEC-RAS software. The selected design flood hydrograph is obtained using Nakayasu Synthetic Unit Hydrograph method by elaborating design rainfall derived from partially series rainfall data frequency analysis of Tondano and Tikala watersheds. Flow simulation is conducted in steps by modeling the hydrograph from Tikala River as the lateral inflow. The first simulation is carried out using bank full capacity discharge to define the flood characteristic and the critical sections. The second simulation is carried out for the design flood hydrograph using unsteady flow calculation on each plan to study the hydraulics feasibility. The study conducted herein is elaborated on water surface profile and velocity due to the plans affectivity to carry-off the flood discharge safely as well as the effect on river uses.Â Based on the existing condition simulation, result shows two reach critical sections of the right bank and one reach critical section of the left bank Tondano River. The results of flood control simulation indicate that there are no significant differences on velocity among plans, but there are disparities on the capacity to carry off flood discharge safely with no overtopping. For the normalization plan, the overtopping is occurred along the critical section, whereas for both dike plan and combination of dike and normalization plan, no overtopping are occurred but the the critical sections are still existed. Revised plans for dike and combination of dike and normalization are equally effective in carrying off flood discharge securely, but have different effects on water utilization during low flow period. Referring to the study result, the best alternative is the revised dike plan.